La litigiosidad en torno a las ventas de oficios perpetuos en la Castilla del siglo xvii - Francisco Andújar Castillo (Les Cahiers de Framespa)
The sale of perpetual offices in the Spanish high Administration during the 17th century generated numerous lawsuits as a result of their high value and of the many privileges and exemptions that were purchased with them. Open disputes on the sales or inheritance rights were common within the institutions. However, the most interesting lawsuits, by far, were initiated by the monarchy itself, always with the intention of raising more money from a property that had been sold many years before. Allegations of fraud - «injury» - filed against buyers reveal that their origin was not the intent of defrauding the purchasers of the property but, most likely, the interest of royal commissioners who attempted to make money through these negotiations in which large sums of money were at stake.